Penerapan Model Small Group Discussion dan Media Uang Koin Serta Dadu untuk Meningkatkan Minat Belajar Matematika pada Materi Peluang Siswa Kelas 6 SD 4 Bulungcangkring - Rohman, Taufiqur; Riswari, Lovika Ardana; Rihayati, Rihayati (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to enhance students' interest in learning mathematics on probability material through the implementation of the Small Group Discussion model and the use of media such as coins and dice. This study is a Classroom Action Research (CAR) conducted in three stages: pre-cycle, cycle I, and cycle II. The subjects of the research are 29 sixth-grade students of SD 4 Bulungcangkring for the 2024/2025 academic year. Data were collected through observations, interest in learning questionnaires, and documentation. The data analysis technique utilized both quantitative and qualitative descriptive techniques. The research results show that there is an increase in student learning interest from the pre-cycle to cycle II. In the pre-cycle, the percentage of students showing high learning interest was 58.62%. After implementing actions in cycle I, the percentage increased to 79.31%, and in cycle II it increased again to 93.10%. The conclusion of this study is that the application of the Small Group Discussion model and the use of media such as coins and cards has proven to be effective in increasing students' interest in learning mathematics on the topic of probability. It is recommended for teachers to apply similar approaches in teaching to motivate students and encourage them to be more active in the learning process.